Avaliação da apoptose nas populações leucocitárias do sangue periférico de pacientes sépticos - Martos, Leandro Silva Willish [UNIFESP] (2010)
Sepsis incidence continues to rise with significant morbidity and mortality and is the leading cause of death in intensive care units. Infection control depends on proper recognition of the microorganisms by immune cells and an adequade effector immune response. Lymphocytes, monocytes and neutrophils are the major peripheral blood cell populations involved in this process. Apoptosis is an important mechanism for controlling the immune response, however, in critical conditions, deregulated apoptosis can lead to immune suppression, difficulting the control of sepsis. This study evaluated the percentage of apoptosis in peripheral blood derived lymphocytes, monocytes and neutrophils by means of exposure of phosphatidylserine on the cell surface and detection of intracellular caspase-3 and evaluated the absolute number and percentage of lymphocytes and their subpopulations by flow cytometry. Forty septic patients were included, of whom, 4 were septic, 9 presented severe sepsis and 27 were in septic shock, classified according to the definitions of the 1992´s consensus. Fifteen healthy volunteers’ were included for comparison. For apoptosis assays, total leucocytes were isolated from the whole blood by hypotonic lysis of the red blood cells and stained with surface antibodies in order to identify the leukocyte subpopulations. For apoptosis evaluation samples were stained with annexin-V and propidium iodide (PI) in an appropriate buffer or labeled with anti-caspase-3 after fixation and permeabilization. Lymphocyte counts were performed in TruCOUNT tubes after labeling the cells with anti-CD45, CD3, CD4, CD8, CD16/56 and CD19. There were no statistical differences in the percentage of apoptosis in total leukocytes, however, lower late apoptosis was observed in T lymphocytes of septic patients when compared to healthy subjects (P<0.05). Septic patients showed a smaller absolute count of total lymphocytes, T lymphocytes, CD4+, CD8+ and NK cells when compared to the healthy individuals (P<0.01), although the percentage of these cell populations has remained unchanged. These results demonstrate that the smallest number of circulating lymphocytes observed during sepsis could not be explained by the presence of apoptosis. The decrease of peripheral blood cell counts could be a result of the cell migration to the lymphoid tissues or organs triggered by infection. There were no differences in the percentage of early apoptosis in neutrophils of patients and healthy individuals. There was a decrease in the percentage of late apoptosis and a consequent increase in the percentage of viable cells in the patients when compared to the healthy subjects (P<0.05). There was no significant differences in the measurement of intracellular caspase-3 in neutrophils of patients compared to the healthy individuals. Analysis of apoptosis during the development os sepsis did not differ among the D0, D7 an D14 groups. There was no difference in the proportion of cells undergoing apoptosis between patients with sepsis who survived and those who died by the twenty-eight (D28) after the diagnosis of sepsis. Late apoptosis in neutrophils appears to be diminished. The possible biological effect of the reduction of apoptosis would be an adapted response to the injury, perhaps extending the half life and activity of neutrophils, however, this decreased apoptosis may contibute to inflammatory injury and predispose to the development of the multiple organ dysfunction syndrome. Only intracellular caspase-3 was evaluated in monocyte population, and no differences were found between this marker on septic patients and healthy individuals. The same results were observed in samples from adminssion, 7 and 14 days of follow-up. The percentage of monocytes with caspase-3 activity on days 0, 7 and 14 of sepsis was related to patient outcome as regards of survival and non-survival, after 28 days of diagnosis. The analysis performed on samples from D0 did not indicate differences in the percentage of apoptotic cells among the survivors and non-survivors. To counterpoint, when this analysis was performed on D7, the percentage of cells positive for caspase-3 were lower in those who died when compared with the survivors after 28 days; besides, this association persisted on 60 and 180 days follow-up. The role of apoptosis in monocytes seems to be important in sepsis, however, further research is needed to elucidate the correlation between monocyte apoptosis and survival.